Algorithm for design of pulse compression radar codes - Raja Rajeswari, K.; Gangatharan, N.; Ezra Morris Abraham, G.; Radha Krishna Rao, G.S.V.; Rani, D.E. (2003)
A new algorithm is proposed for the design of radar pulse compression codes from the known Baumert codes using cyclic shifting and modular permutation techniques.